"Erase/rewind": How transgender Twitter discourses challenge and (re)politicize lesbian identities. Issue 2 (29th March 2022) - Webster, Lexi
Abstract: Competing views on the in/compatibility of transgender status and lesbian identity is a source of conflict in the ongoing antagonism over transgender recognition. Many individuals with different transgender identities might lay claim to lesbian identity or lesbian discourse(s) more generally. However, this inclusion has been disputed in some circles insofar as it is seen to challenge or contradict characteristics of lesbianism. This paper explores how transgender discourses might challenge and (re)politicize lesbianism and lesbian identities. Given that social media platforms concentrate minority communities in one space and can serve to exacerbate antagonism over identities, I focus in this paper specifically on the Twitter context. This paper uses corpus-informed critical discourse studies to explore how cognitive models of lesbianism are articulated in transgender Twitter discourse/s. Findings indicate that transgender Twitter users (re)articulate sociohistorical narratives in lesbian discourse/s. At the same time, however, they also challenge and (re)politicize the essentialism of sex and gender in relation to lesbian identity and social practice. Hence, transgender Twitter discourse/s reflect potential explanations for contesting transinclusion in lesbianism, which may serve to reinforce transexclusionary claims for retaining lesbianism's uniqueness as a female space and experience.